Pengaruh Pemanfaatan Kulit Kerang Sebagai Pengganti Sebagian Agregat Halus dengan Menggunakan Pasir Pantai Terhadap Kuat Tekan Beton dan Mutu K-200 - Ramadhan, Sya'i; Arif, Samsul (Universitas Batanghari Jambi, 2024)
The influences of shells utilization as smooth aggregate replacement by using sands beach on the concrete compressive strength and the quality of k-200, the use of smooth aggregate substitutes, such as manually broken clam shells and beach sand obtained from Paciran, Lamongan Regency. The mixture used in making concrete is concrete with quality K-200 (fc'16.60 Mpa). Concrete sand will be replaced by 50% with beach sand, and mixed variations will be carried out with the addition of shells by 10%, 15%, and 20%. The test results show that the average compressive strength of normal concrete is 16.60 Mpa. For a mixture with shell waste by 10% and sea sand by 50%, the average compressive strength value is 15.09 Mpa. In a mixture with shell waste by 15% and sea sand by 50%, the average compressive strength value is 14.62 Mpa. While in a mixture with shellfish waste of 20% and sea sand of 50%, the average compressive strength value is 14.13 Mpa. The concrete variant with the highest average compressive strength value is the normal variant with a value of 16.60 Mpa, while the concrete variant with the lowest average compressive strength value is the variant with shell waste of 20% and sea sand of 50%, with a value of 14.13 Mpa.